Rekonstruksi Ontologi Bencana Banjir di Indonesia: Dari Fatalisme Menuju Resiliensi Berbasis Sains - Muhammad Gusti; Syukri Syukri; Rahmad Salam; Andriansyah Andriansyah (MAN 4 Kota Pekanbaru, 2026)
This study examines how disaster ontology shapes the ways flood risks are understood and governed in flood-prone regions. Using a qualitative critical–interpretive approach, the research analyzes community narratives, institutional practices, and policy documents to uncover the dominance of fatalistic interpretations that frame floods as unavoidable destiny. Such views reproduce reactive responses and weaken the institutionalization of disaster science in planning and risk management. The findings also reveal emerging elements of a science-based resilience ontology, reflected in community initiatives, the use of risk data, and limited cross-actor collaboration. The study argues that reconstructing disaster ontology is a fundamental prerequisite for building adaptive and equitable flood risk governance. Integrating scientific knowledge, transforming perspectives, and strengthening collaborative governance are essential to shift from reactive disaster management toward long-term, science-informed resilience.